Criminal Law and Digital Technologies: An Institutional Approach to Rule Creation in a Rapidly Advancing and Complex Setting - Fehr, Colton (McGill Law Journal / Revue de droit de McGill, 2019)
Courts and legislatures in Canada and around the world have struggled to respond effectively and efficiently to the challenges posed by the use of rapidly advancing and complex technologies. As a result, scholars have debated the appropriate role of each institution with respect to governing privacy in the digital age. This debate has provided foundational evidence upon which to develop a normative framework for governing digital privacy. Yet, the Canadian literature has only sparsely addressed the ability of Canadian legislatures to respond to the challenges presented by the use of digital technologies. This article begins to fill the gap in the literature by asking whether Parliament has been able to reply to the use of complex and rapidly advancing technologies in an efficient, coherent, and fair manner. I conclude that Parliament’s legislative framework for governing state intrusions into digital privacy has been patchwork and inconsistent. After comparing these findings to the literature on the relative institutional capacity of courts, I outline a general strategy for ensuring each institution tasked with governing digital privacy is working to its strengths, not its weaknesses.